2003
DOI: 10.1063/1.1600843
|View full text |Cite
|
Sign up to set email alerts
|

Early stage of plastic deformation in thin films undergoing electromigration

Abstract: Electromigration occurs when a high current density drives atomic motion from the cathode to the anode end of a conductor, such as a metal interconnect line in an integrated circuit. While electromigration eventually causes macroscopic damage, in the form of voids and hillocks, the earliest stage of the process when the stress in individual micron-sized grains is still building up is largely unexplored. Using synchrotron-based x-ray microdiffraction during an in-situ electromigration experiment, we have discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…[2][3][4] Recently, a very early stage of plastic deformation and microstructural evolution during an electromigration test was detected in Al(Cu) interconnect lines, long before any macroscopic damages become visible, by using a synchrotron technique involving white beam X-ray microdiffraction. 5 In particular it was observed that during in-situ electromigration a gradient of plastic deformation evolves along the line which results in bending and in polygonization of the largest grains between the cathode and the anode end. Smaller grains do not readily deform but do rotate as electromigration proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Recently, a very early stage of plastic deformation and microstructural evolution during an electromigration test was detected in Al(Cu) interconnect lines, long before any macroscopic damages become visible, by using a synchrotron technique involving white beam X-ray microdiffraction. 5 In particular it was observed that during in-situ electromigration a gradient of plastic deformation evolves along the line which results in bending and in polygonization of the largest grains between the cathode and the anode end. Smaller grains do not readily deform but do rotate as electromigration proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…Kirchheim and Kaeber 2 attributed this extra depression of MTF in the high j range to a Joule heating effect. Our earlier studies [12][13][14] have also suggested electromigration-induced plasticity that can lead to new paths for EM transport which could also be responsible for this deviation. 8 It is certainly within the range of possibilities that either one of these effects dominates or that both effects contribute to various different extents to the MTF deviation from the n = 1 line at the high j range.…”
Section: Resultsmentioning
confidence: 87%
“…Joule heating is widely believed to be the source of this deviation, as suggested by Kirchheim and Kaeber, 2 especially in the case of Al interconnects. However the recent discovery of EM-induced plasticity, [12][13][14] wherein plastic deformation leads to new paths for EM transport, could also cause this deviation. 8 Plastic deformation behavior in metallic interconnect lines during EM experiments has been observed in both Al 12,14 and Cu interconnects, 8,13 using a synchrotron technique involving white-beam x-ray microdiffraction that can function as a local probe of plastic deformation in crystals that compose the interconnect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…White light synchrotron X-ray microdiffration has been applied for the purpose of visualizing the grain morphology and estimating the strain occurring under electromigration. 11,12 In situ scanning electron microscope (SEM) investigations have revealed that dissolution phenomena occur in the second phases of 95Pb5Sn 13 and Sn0.8Cu 14,15 solders under electric current. Electrorecrystallization was observed in the second phases after the current was stopped.…”
mentioning
confidence: 99%